Phytochemical constituents of Dracaena mahatma leaves and their anti-bacterial, anti-oxidant and anti-inflammatory significance. Issue 1 (January 2018) - Shankar, Saranya; Settu, Sugashini; Segaran, Gayathri; Sundar, Ranjitha Dhevi V.; Ravi, Lokesh
Abstract: The present study aims to analyze the antimicrobial, antioxidant and anti-inflammatory activity of Dracaena mahatma leaf extract. Qualitative phytochemical screening of leaf powder confirmed the presence of tannins, alkaloids, phenols, terpenoids, sterols, triterpenes and anthraquinone glycosides. GC-MS analysis of methanolic extract suggested the presence of 2 unknown compounds and 8 known phytochemicals, of which benzene-(1, 6-hexanediylidene)tetrakis constituted a maximum percentage of the crude extract. The total phenolic content of the crude extract was found to be 32.9 ± 0.002 GAE/g. Crude extract demonstrated 90% antioxidant activity in DPPH assay at 100 μg/ml concentration and also demonstrated significant antioxidant activity in FRAP assay at 100 μg/ml concentration. The crude extract did not show any antagonism against fungal pathogens Aspergillus niger and Aspergillus flavus . Crude extract demonstrated significant antibacterial activity against 5 studied pathogen, with the highest antagonism against Escherichia coli with a zone of inhibition of 22 mm at 10 mg/well concentration.